Analysis of entropy generation in the nonlinear thermal radiative micropolar nanofluid flow towards a stagnation point with catalytic effects. (1st August 2022) - Ishtiaq, Bushra; Zidan, Ahmed M; Nadeem, Sohail; Kbiri Alaoui, Mohammed
Abstract: The major goal of this work is to analyze the entropy generation in a micropolar nanofluid's hydromagnetic stagnation point flow with the involvement of the catalytic and nonlinear thermal radiation effects. The magnetite nanoparticle Fe 3 O 4 is added to the water to form the Fe 3 O 4 -water nanofluid. A vertical stretchable sheet is assumed to initiate the two-dimensional time-independent flow. The impacts of Joule heating and viscous dissipation are considered in the development of the governing equations of the concerned problem. An appropriate procedure of similarity transformations is implemented in the system of partial differential equations (PDE) to establish the nonlinear setup of ordinary differential equations (ODE). The behavior of various aspects of fluid such as micro-rotation, entropy generation, temperature, velocity, Bejan number, and concentration relative to the pertinent parameters is graphically revealed. The graphical nature of local Nusselt number and skin friction relative to the physical parameters is also exhibited in this analysis. This study concludes that the amplification in the magnetic field develops a minimization in the velocity field. The Bejan number shows the declining behavior corresponding to the larger quantities of the Brinkman number and Reynolds number, but the entropy of the system escalates for these parameters.